Hybrid Reinforcement Learning Architecture with Geometric Curriculum Learning for Non-Holonomic Leader-Follower Navigation - Caxias, Natasha Araújo; Rocha, Abel Severo; Carvalho, José Reginaldo Hughes (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This paper proposes a hybrid architecture for leader-follower non-holonomic navigation, combining a Dueling Deep Q-Network (DDQN), Prioritized Experience Replay (PER), Frame Stacking, and Golden Ratio action discretization. A three-phase Geometric Curriculum Learning strategy addresses sparse rewards and catastrophic forgetting, progressing from fixed geometries to full Domain Randomization. Ablation studies confirm that Frame Stacking and Golden Ratio discretization are strictly necessary, their removal collapses success to 0%, while PER acts as a convergence accelerator rather than a behavior enabler. The full system achieves 100% success on fixed configurations and 74% on procedural generalization.